Income Splitting - is it Good for Both Partners in the Marriage? - Matthias Wrede (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper analyzes the effects of an income splitting system on marriage partners. The focus is on the time allocation, on investment in marriage-specific human capital and on the distribution of income within the family. Two insights are discussed in detail. First, the distribution of tax-reduction gains due to the income splitting system depends on whether the family has been started or not. After marriage, joint taxation increases redistribution among family members. Second, although the income splitting system reduces the tax burden of the family, it might harm the marriage partner that is more productive in household production provided that potential marriage partners foresee the effects of joint taxation on the family.
Keywords: 330; Income taxation; income splitting; private provision of public goods; household production